PENDAPATAN DAN STRATEGI PENGEMBANGAN USAHA INTEGRASI SAPI POTONG PADA TANAMAN KAKAO DI KABUPATEN BOALEMO GORONTALO - Hildah Khurniyah; Zulzain Ilahude; Muhammad Mukhtar (JURNAL GALUNG TROPIKA, 2019)
The implementation of the cocoa and cattle integration system is expected to reduce agricultural production costs and livestock business costs due to the availability of feed ingredients for livestock and sources of fertilizer for cocoa plants. This study aims to analyze the income of farmers who apply the system integration pattern for beef cattle in cocoa. In addition to analyzing strategies that must be applied by beef cattle breeders in the cocoa crop integration pattern. The study was conducted in Paguyaman and Wonosari Districts, Boalemo District, with a sample of 103 farmers. Analysis of the data used is a descriptive analysis of income and SWOT. The results showed that farmers' income in the integration pattern had good progress where the R / C ratio of cocoa plants had increased income by 23.48% from non-integration into integration. While for cattle, there was an increase in income of 2.39%. In addition, a strategy to develop the integration of beef cattle-cacao is in quadrant 3, a WO strategy that combines opportunities to reduce farmers' weaknesses in developing integrated beef cattle systems in crops. cocoa in Boalemo District.